Diseño y construcción de una tarjeta electrónica para generación y control de ondas eléctricas de inmovilización humana usadas en dardos inalámbricos (2014)
CEW human electroconduction weapons are widely used devices for the control of highly dangerous situations such as mutinies, hostage takings or suicide attempts whose outcome is usually the loss of life or the occurrence of important injuries. The use that these devices make of the electrical conduction characteristics of the human body through the distortion in the neuronal signals that control muscle activity, constitutes a highly effective principle in order to achieve the temporary immobilization of the human being, allowing In this way, to carry out the physical control of the individual and the dissolution of the risk situation, however, the exposure to excessive levels in some electrical variables can end up causing lethal effects. This document intends to carry out, on the one hand, a theoretical approach to the characteristics that make these devices dangerous elements and those that are desirable in an effective and safe weapon, and on the other, seeks to expose a practical approach to the technological resources necessary for the design and construction of an electrical wave generator device for human immobilization, aimed at studying the effectiveness and safety of electrical signals that can provide minimum energy and long range application conditions such as those possibly used in wireless electronic darts. The text exposes progressively the development of the investigative activity, from the approach to the problem, the documentary exploration related to the electrical phenomena in the human body and the effects produced by the CEW devices, identifying those technologies that show, in the light of scientific considerations, cause the desired effects of immobilization and maintain a minimum risk for the health of the human being. Subsequently, the technological considerations necessary for the practical development of the device generating such waves are outlined, describing the theoretical tools and the process of design and instrumental exploration required for the construction of the prototype. In chapter one, aspects such as the definition and justification of the problem, the objectives and scope of the work are exposed. Chapter two relates the theoretical elements that describe the behavior of the human body to the electrical stimuli produced by the CEW devices and the legal aspects of their use. Chapter three indicates the work methodology and alternatives selected for the prototype implementation. Chapter four describes the procedures for designing the necessary stages and their final integration. Chapter five corresponds to the development of the performance tests performed on the final team implemented and finally in chapter six the presentation of conclusions, results and contributions of the work is made.